Social Movement Innovation Berbasis Jabar Quick Response di Jawa Barat menggunakan Analisis Agile Governance - Nunung, Ai; Latifah, Latifah; Fatmawati, Fatmawati (Kolaborasi : Jurnal Administrasi Publik, 2024)
This research aims to analyse the application of Agile governance principles in Jabar Quick Response as a channel for social and humanitarian complaints for the people of West Java. The research used descriptive qualitative research. The data sources in this study consist of primary data and secondary data. Data collection techniques used observation, interview, and document data collection methods. The results indicate that the implementation of Agile governance principles in Jabar Quick Response is still experiencing obstacles due to several existing problems. On the principle of Good Enough Governance, although governance is adapted to the organisational context, the main problem is the lack of human resources in Jabar Quick Response. For the principle of business-driven, although Jabar Quick Response has focused on business orientation, budget limitations hinder its enforcement. Meanwhile, on the human-focused principle, Jabar Quick Response has succeeded in making individuals, both members and communities, feel valued.